2013
DOI: 10.3892/etm.2013.1183
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexmedetomidine in coronary artery bypass grafting surgery

Abstract: The aim of this study was to observe the impact of dexmedetomidine on postoperative myocardial injury in patients undergoing off-pump coronary artery bypass (OPCAB) grafting. One hundred and sixty-two patients who were undergoing OPCAB surgery were randomly divided into control and dexmedetomidine groups (groups C and Dex, respectively). Following the first vascular anastomosis grafting, the patients in group Dex received a continuous intravenous infusion of 0.2–0.5 μg/kg/h dexmedetomidine, until they were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 32 publications
4
83
1
Order By: Relevance
“…Depletion of Se state during the surgery triggers neutrophil accumulation in reperfused sites, which is the primary source of ROS and proteolytic enzyme generation (39). Crucially, the myocardial injury has been measured by serum cardiac enzymes (5,40). Although the value of cardiac biomarkers for adverse outcome following CABG is poorly understood, it is suggested that among myocardial necrosis markers, cardiac troponins are the gold standard for detection of the cardiac damage (9, 32) Multiple Tn isoforms have been detected in muscles, but CTnT and CTnI are known as cardiac specific isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Se state during the surgery triggers neutrophil accumulation in reperfused sites, which is the primary source of ROS and proteolytic enzyme generation (39). Crucially, the myocardial injury has been measured by serum cardiac enzymes (5,40). Although the value of cardiac biomarkers for adverse outcome following CABG is poorly understood, it is suggested that among myocardial necrosis markers, cardiac troponins are the gold standard for detection of the cardiac damage (9, 32) Multiple Tn isoforms have been detected in muscles, but CTnT and CTnI are known as cardiac specific isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial reperfusion itself causes tissue damage, which is known as an ischemic/reperfusion (I/R) injury (1)(2)(3)(4)(5). Accumulating evidence suggests that generation of reactive oxygen species (ROS) following neutrophil activation and inflammatory reactions is the main triggering factor of the I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate, lactate, glucose, and insulin are respiratory substrates indicating heart perfusion. The level of pyruvate in the blood increases in the anaerobic state and pyruvate is converted to lactate under these conditions (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Eliminating or reducing myocardial injury can improve the clinical prognosis of patients undergoing cardiac surgery. Cardiac biomarkers are associated with the degree of cardiac injury and cardiac troponin I (cTnI), lactate, and creatine phosphokinase-MB (CKMB) are especially sensitive biomarkers for evaluating cardiac cell damage (2)(3)(4). Pyruvate, lactate, glucose, and insulin are respiratory substrates indicating heart perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Perianesthetic use of dexmedetomidine has a hemodynamic stability effect, which is associated with a decrease in postoperative mortality and reduction in the incidence of postoperative complications (Ji et al, 2013;Shin et al, 2013). The protective effects of dexmedetomidine on postoperative myocardial injury have been defined (Ren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%